Fully Solution‐Processed TCO‐Free Semitransparent Perovskite Solar Cells for Tandem and Flexible Applications. Issue 1 (1st September 2017) - Zhang, Yaokang; Wu, Zhongwei; Li, Peng; Ono, Luis K.; Qi, Yabing; Zhou, Jixiang; Shen, Hui; Surya, Charles; Zheng, Zijian
Abstract: Semitransparent perovskite solar cells (st‐PSCs) have received remarkable interest in recent years because of their great potential in applications for solar window, tandem solar cells, and flexible photovoltaics. However, all reported st‐PSCs require expensive transparent conducting oxides (TCOs) or metal‐based thin films made by vacuum deposition, which is not cost effective for large‐scale fabrication: the cost of TCOs is estimated to occupy ≈75% of the manufacturing cost of PSCs. To address this critical challenge, this study reports a low‐temperature and vacuum‐free strategy for the fabrication of highly efficient TCO‐free st‐PSCs. The TCO‐free st‐PSC on glass exhibits 13.9% power conversion efficiency (PCE), and the four‐terminal tandem cell made with the st‐PSC top cell and c‐Si bottom cell shows an overall PCE of 19.2%. Due to the low processing temperature, the fabrication of flexible st‐PSCs is demonstrated on polyethylene terephthalate and polyimide, which show excellent stability under repeated bending or even crumbing. Abstract : Fully solution‐processed transparent conducting oxide‐free semitransparent perovskite solar cells are reported to allow low‐cost fabrication of highly efficient tandem solar cells and flexible solar cells. Nitric acid annealed poly(3, 4‐ethylenedioxythiophene): polystyrene sulfonate is incorporated in the fabrication process to realize high‐throughput printing of highly conductive transparent electrodes.